Mental Health Nurses' Experiences of Working in the Emergency Department of Two Rural Australian Settings. (3rd October 2021) - Wand, Timothy; Collett, Gemma; Keep, Joel; Cutten, Alexa; Stack, Amanda; White, Kathryn
Abstract: Providing effective mental health care in Emergency Departments (ED) is a fundamental expectation, as EDs increasingly become the first point of contact with health services for people in mental distress. As part of a larger multi-site translational research project this study explored the experiences, perspectives and recommendations of mental health liaison nurses (MHLN) employed in the EDs of two rural hospitals in New South Wales, Australia. Participants identified numerous benefits associated with embedding the MHLNs within the ED team. Some challenges associated with changing thinking and practice were recognised and recommendations for improving ED mental health care provided.